(untitled) (Global Journal of Management and Business Research, 2014)
The aim of this paper is to investigate the lead-lag effect on the predictability of returns. This analysis is applied to daily and one-minute interval data on the TAIWAN stock market. The results indicate evidence of predictability between indices with different degrees of liquidity and when considering one-minute interval data.